Комплексний метод оптимізації маршрутизації інформаційних потоків у самоорганізованих мережах - Климаш, Ю. В.; Шпур, О. М.; Кайдан, М. В.; Klymash, Yu. V.; Shpur, O. M.; Kaidan, M. V. (Видавництво Львівської політехніки, 2017)
Розроблено комплексний підхід до оптимізації маршрутів передавання даних у самоорганізованих мережах. Суть методу полягає у оптимізації множини найкращих маршрутів, що утворюються завдяки роботі модифікованих алгоритмів імітації відпалу та мурашкового, використання яких дає змогу знаходити глобальний екстремум деякої функції на основі впорядкованого випадкового пошуку та здійснювати пошук оптимізованого маршруту з найкращим значенням параметра QoS на основі видалення/додавання вузла до маршруту, а також враховувати неоднорідності в мережі. Це дасть змогу забезпечити високу працездатність мережі загалом та підтримувати необхідний рівень параметрів QoS для кінцевих користувачів.

Modified routing algorithms are presented based on basic meta-heuristic algorithms: ant colony optimization, genetic and simulated annealing to determine the best route for information flows in self-organized networks. An ant colony optimization is based on the use of the probability parameter for the transition between the nodes located between the source node and the receiving node. To solve the problem of optimization of routing in a simulated annealing, its modification is proposed by adding or removing a transit node based on the coverage of the reaching range of neighboring nodes. As a target function for estimating a route, the QoS parameter is considered – the time of data delivery from the source node to the receiving node. For the first time, a routing algorithm is proposed based on a combination of proposed modified algorithms, where, from a set of best routes, formed by a modified annealing simulation algorithm, the choice of the best route according to the criterion of the time of data transmission is made by using a modified ant algorithm. For simulation an algorithm for generating traffic of a self-organized network is presented. The considered algorithms of routing allow to reduce the time of data transmission between the source node and the receiving node, which increases the efficiency of routing information flows in selforganized networks. It is shown that an important condition for efficient routing in selforganized networks is the reduction of the number of transit nodes between the source node and the node-coordinator.
Complex optimization method of routing information flows in self-organized networks
Keywords: самоорганізовані мережі; мурашковий алгоритм; генетичний алгоритм; метод імітації відпалу; QoS; self-organized networks; ant colony optimization; genetic algorithm; simulated annealing; QoS; 621.391